Proposal of a Java Front-end for voice synthesizer based on MBROLA - NÃcolas de AraÃjo Moreira (2015)
It is estimated that, in Brazil, about 3.46% of population presents difficulty to see and 1.6% is blind. The lack of adequate inclusive tools imposes many restrictions on the life of these people, in other words, non-accessible hardware and software create a negative impact on academic, professional and personal life. In this context, the present thesis aims to develop a an accessible system for digital inclusion of blind users, since the existing systems present many disadvantages as low quality or cost that make impossible the daily use. The system is composed by a multiplatform Java front-end. In addition, the system is free to reach the maximum numbers of users as possible and to be modified and improved by the community. The developed solution was tested, presenting a medium intelligibility rate of 79% and naturalness classified as "reasonable" by a group of 20 users. In the end, the system proved to be feasible, filling an existing gap on Brazilian software marked, allowing greater inclusion of blind users to digital resources.